2014
DOI: 10.1055/s-0034-1383262
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antihyperlipidemic Potential of Triterpenes from Stem Bark of Protorhus longifolia

Abstract: Two lanostane triterpenes, 3β-hydroxylanosta-9,24-dien-21-oic acid (1) and methyl-3β-hydroxylanosta-9,24-dien-21-oate (2), were isolated from the stem bark of Protorhus longifolia. Their structures were deduced on the basis of spectroscopic analysis (NMR, HRMS, IR). This study investigated the in vitro anti-adipogenic activity of the two triterpenes. Their inhibitory activity was evaluated on selected lipid digestive enzymes (pancreatic lipase and cholesterol esterase). The inhibitory activity of the compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 25 publications
5
23
0
1
Order By: Relevance
“…RA-3 was routinely isolated and purified from the chloroform extract of P. longifolia stem bark using chromatographic techniques. The physical (white crystals, >95% pure, melting point 204–205 °C) and spectral data (IR (KBr) v max = 3469, 1683 cm –1 , molecular formula C 31 H 50 O 3 ) of this compound were in agreement with previous reports from our laboratory [ 14 , 18 ]. The expected chemical structure of the compound was confirmed as methyl-3β-hydroxylanosta-9,24-dien-21-oate ( Figure 1 ).…”
Section: Resultssupporting
confidence: 91%
“…RA-3 was routinely isolated and purified from the chloroform extract of P. longifolia stem bark using chromatographic techniques. The physical (white crystals, >95% pure, melting point 204–205 °C) and spectral data (IR (KBr) v max = 3469, 1683 cm –1 , molecular formula C 31 H 50 O 3 ) of this compound were in agreement with previous reports from our laboratory [ 14 , 18 ]. The expected chemical structure of the compound was confirmed as methyl-3β-hydroxylanosta-9,24-dien-21-oate ( Figure 1 ).…”
Section: Resultssupporting
confidence: 91%
“…Engl. ( Anacardiaceae ) possesses a broad spectrum of biological properties, including in vivo hypolipidemic and hypoglycemic properties [ 23 , 24 , 25 , 26 , 27 ]. We have already reported that RA-3 administration for 14 days suppressed glucose levels and increased hepatic glycogen content in streptozotocin (STZ)-induced diabetes in rats [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, a captação de glicose também melhorou em células musculares C 2 C 12 . 40 Outros triterpenos do tipo lanostano, isolados de Ganoderma lucidum também mostraram efeito de inibição da diferenciação das células 3T3-L1, evidenciado pela redução do acúmulo de lipídeos. 41 Uma revisão de literatura mostrou diversos estudos realizados com triterpenos ginsenosídeos, principais constituintes do ginseng (raíz da espécie Panax ginseng), sobre a obesidade (in vivo) e a adipogênese (in vitro).…”
Section: Antiadipogênicaunclassified